2021
DOI: 10.1055/a-1373-5523
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Relapse of Hyperthyroidism in Treated Graves’ Disease with Orbitopathy by Serial Measurements of TSH-Receptor Autoantibodies

Abstract: The aim of this study was to investigate the potential of the new TSH-receptor antibody (TRAb) assays to predict remission or relapse of hyperthyroidism in patients with Graves’ disease (GD) and Graves’ orbitopathy (GO). TRAbs were measured retrospectively in sera from a cohort of GD patients with GO (n=117; remission n=38 and relapse n=79–Essen GO biobank) with automated binding immunoassays: TRAb Elecsys (Cobas Roche) and TRAb bridge assay (IMMULITE, Siemens), and the TSAb (thyroid stimulating Ab) cell-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(57 reference statements)
0
7
0
1
Order By: Relevance
“…In addition, unlike binding assays, functional biomarkers have demonstrated remarkable predictive value as indicators of relapse/remission of GD and the clinical phenotype of TAO [27] [43] [44] . This is another feature in favor of bioassays that would greatly facilitate patient monitoring and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike binding assays, functional biomarkers have demonstrated remarkable predictive value as indicators of relapse/remission of GD and the clinical phenotype of TAO [27] [43] [44] . This is another feature in favor of bioassays that would greatly facilitate patient monitoring and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…TRAbs in the serum samples of Graves hyperthyroidism are polyclonal and may contain apparent neutral Abs (or short-acting TBAb) in addition to TSAb and TBAb (long acting). Therefore, the measurement of TSAbs is useful to assess the remission of the patient after treatment with antithyroid drugs [ 25 ]. For a complete understanding of TRAb, the isolation of apparent N-mAb is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the treatment of the GO, decisions have to be made again and again for the patients. Identification of relapsing hyperthyroidism was possible with automated immunoassays and cell-based bioassay especially with serial TRAb measurements during the course of ATD therapy [40] . Bartalena et al (2017) has shown in the dose finding study for i. v. glucocorticoid treatment that after 6 weeks treatment one can already see a trend whether i. v. glucocorticoid treatment will deliver the desired treatment success [41].…”
Section: Discussionmentioning
confidence: 99%